A Content Analysis of English Textbook “Bright An English” Used in Second Grade Junior High School Based on Merdeka Curriculum - Nurhayati Tuluki; Harni Jusuf; La aba; Andi Nurwati; Enni Akhmad (Journal of English Teaching and Linguistic Issues (JETLI), 2025)
In the context of educational reform in Indonesia, the implementation of the Merdeka Curriculum has brought significant changes over the past few decades. A crucial aspect of this transformation is the curriculum for students, aimed at equipping them with the knowledge and skills necessary to become productive members of society. Launched by the Ministry of Education in 2020, the Merdeka Curriculum emphasizes a more holistic and inclusive educational approach, focusing on student-centered learning and technology use. This study aims to analyze the alignment of the textbook "Bright An English" with the Merdeka Curriculum for second-grade junior high school students, identifying its strengths and weaknesses in supporting English language learning. A qualitative approach was employed, specifically through document analysis. This method is often used to analyze written or visual data to identify specific characteristics or materials, focusing on the English textbook "Bright An English". The analysis revealed that the textbook generally meets the English language competencies outlined in the Merdeka Curriculum. Students are able to engage with various types of texts and develop their language skills effectively. However, areas such as the integration of character values and cultural diversity in the teaching materials require improvement. The findings indicate that "Bright An English" is largely aligned with the Merdeka Curriculum, fulfilling many essential requirements. Despite some shortcomings, the textbook remains a valuable resource for teachers and students, and supplementary materials are recommended to enhance the learning experience. Overall, it provides a solid foundation for English language education at the junior high school level.